Erratum: Addressing the Challenges of Extension and Advisory Services in Uganda: The Grameen Foundation’s Community Knowledge Worker Program - JIAEE Editors (Journal of International Agricultural and Extension Education, 2024)
Correction: The DOI of the article "McCole, D., Culbertson, M. J., Suvedi, M., & McNamara, P. E. (2014). Addressing the Challenges of Extension and Advisory Services in Uganda: The Grameen Foundation’s Community Knowledge Worker Program. Journal of International Agricultural and Extension Education, 21(1), 6-18” was incorrect as published. The correct DOI is: 10.5191/jiaee.2014.20101